Central Mechanisms for Exercise Training-Induced Reduction in Sympatho-Excitation in Chronic Heart Failure - Haack, Karla K.V. (Auton Neurosci, 2014)
The control of sympathetic outflow in the chronic heart failure state (CHF) is markedly abnormal. Patients with heart failure present with increased plasma norepinephrine and increased sympathetic nerve activity. The mechanism for this sympatho-excitation are multiple and varied. Both depression in negative feedback sensory control mechanisms and augmentation of excitatory reflexes contribute to this sympatho-excitation. These include the arterial baroreflex, cardiac reflexes, arterial chemoreflexes and cardiac sympathetic afferent reflexes. In addition, abnormalities in central signaling in autonomic pathways have been implicated in the sympatho-excitatory process in CHF. These mechanisms include increases in central Angiotensin II and the Type 1 receptor, increased in reactive oxygen stress, up regulation in glutamate signaling and NR1 (N-methyl-D-aspartate subtype 1) receptors and others. Exercise training in the CHF state has been shown to reduce sympathetic outflow and result in increased survival and reduced cardiac events. Exercise training has been shown to reduce central Angiotensin II signaling including the Type 1 receptor and reduce oxidative stress by lowering the expression of many of the subunits of NADPH oxidase. In addition, there are profound effects on the central generation of nitric oxide and nitric oxide synthase in sympatho-regulatory areas of the brain. Recent studies have pointed to the balance between Angiotensin Converting Enzyme (ACE) and ACE2, translating into Angiotensin II and Angiotensin 1–7 as important regulators of sympathetic outflow. These enzymes appear to be normalized following exercise training in CHF. Understanding the precise molecular mechanisms by which exercise training is sympatho-inhibitory will uncover new targets for therapy.